ENHANCE OF SOCIAL MEDIA VALUES OF NAQSYABANDIYAH TARGET PRACTICES IN MERANTI ASAHAN VILLAGE - Sapta Yuni Achirani Purba; Syarifuddin; Fuji Rahmadi P (INFOKUM, 2022)
This study aims to discuss the importance of instilling social values, especially for the practitioners of the Naqsyabandiyah Order in Meranti Village, Asahan Regency. These social values ​​become a measuring tool for a value to remain harmonious between citizens. This study uses a descriptive qualitative method approach, meaning that this research focuses on existing phenomena then understood and analyzed in depth, in data collection techniques the researchers used observation and interview techniques. The results of this study illustrate that the community, especially the practitioners of the Naqsyabandiyah Order in Meranti Village, upholds social values ​​in a social scope. family